2017
DOI: 10.1371/journal.pone.0189753
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of scientific research literature and strategies for reading papers depend on academic career stage

Abstract: Reading primary research literature is an essential skill for all scientists and students on science degree programmes, however little is known about how researchers at different career stages interact with and interpret scientific papers. To explore this, we conducted a survey of 260 undergraduate students and researchers in Biological Sciences at a research intensive UK university. Responses to Likert scale questions demonstrated increases in confidence and skill with reading the literature between individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 29 publications
0
67
0
18
Order By: Relevance
“…Most of the questions related to these skills involve experimental data or scientific information in the passage and ask a student to solve a problem using the given information, relying on basic knowledge. Reading current scientific research literature and applying strategies such as selective and critical reading, assessing the authors conclusions, and identifying key ideas in the paper will benefit students through application of scientific reasoning and problem solving [32].…”
Section: Testingmentioning
confidence: 99%
“…Most of the questions related to these skills involve experimental data or scientific information in the passage and ask a student to solve a problem using the given information, relying on basic knowledge. Reading current scientific research literature and applying strategies such as selective and critical reading, assessing the authors conclusions, and identifying key ideas in the paper will benefit students through application of scientific reasoning and problem solving [32].…”
Section: Testingmentioning
confidence: 99%
“…The most difficult item in statistical literacy is -data interpretation‖. Lie et al (2016) and Hubbard and Dunbar (2017) revealed postgraduate students perceived that interpreting -experimental data‖ are difficult. This study proved that students are weak at interpreting results from table or graph.…”
Section: Table 3 Threshold Logit Of Research Literacy Levelmentioning
confidence: 99%
“…Of the necessary transferable and research skills, the art of reading and understanding primary research papers is of upmost importance for developing thinking skills related to the scientific process. Nevertheless, undergraduate students find this difficult despite the availability of numerous resources and support, and consequently, scientific reading ability develops slowly over a scientific career (Hubbard & Dunbar, 2017). There is no doubt that it is important for science undergraduate students to immerse themselves in the primary research literature, and the intricacies of reading, interpretation and critical appraisal, as soon as is possible so they develop these competencies (Wenk & Tronsky, 2011).…”
Section: Developing Science Communication Skillsthe Contextmentioning
confidence: 99%